The onset of pediatric refractory status epilepticus is not distributed uniformly during the day. (August 2019) - Sánchez Fernández, Iván; Gaínza-Lein, Marina; Abend, Nicholas S.; Amengual-Gual, Marta; Anderson, Anne; Arya, Ravindra; Brenton, J. Nicholas; Carpenter, Jessica L.; Chapman, Kevin E.; Clark, Justice; Farias-Moeller, Raquel; Davis Gaillard, William; et al.
Highlights: There is limited data on the distribution of status epilepticus during the day and night. The onset of pediatric refractory status epilepticus (rSE) is related to time of day. The distribution of onsets of rSE is not uniform. The distribution of rSE onset has a peak in the morning (11am−12 pm) and trough at night (11 pm–12 am). Abstract: Purpose: To evaluate whether the onset of pediatric refractory status epilepticus (rSE) is related to time of day. Method: We analyzed the time of day for the onset of rSE in this prospective observational study performed from June 2011 to May 2019 in pediatric patients (1 month to 21 years of age). We evaluated the temporal distribution of pediatric rSE utilizing a cosinor analysis. We calculated the midline estimating statistic of rhythm (MESOR) and amplitude. MESOR is the estimated mean number of rSE episodes per hour if they were evenly distributed. Amplitude is the difference between MESOR and maximum rSE episodes/hour, or between MESOR and minimum rSE episodes/hour. We also evaluated the temporal distribution of time to treatment. Results: We analyzed 368 patients (58% males) with a median (p25 – p75 ) age of 4.2 (1.3–9.7) years. The MESOR was 15.3 (95% CI: 13.9–16.8) and the amplitude was 3.2 (95% CI: 1.1–5.3), p = 0.0024, demonstrating that the distribution is not uniform, but better described as varying throughout the day with a peak in the morning (11am–12 pm) and trough at night (11 pm–12 am). The duration from rSE onset to application of the first non-benzodiazepine antiseizure medication peaked during the early morning (2am–3 am) with a minimum during the afternoon (2 pm–3 pm) ( p = 0.0179). Conclusions: The distribution of rSE onset is not uniform during the day. rSE onset shows a 24-h distribution with a peak in the mid-morning (11am–12 pm) and a trough at night (11 pm-12am).